Unresolved Trauma and Reorganization in Mothers: Attachment and Neuroscience Perspectives - Iyengar, Udita; Rajhans, Purva; Fonagy, Peter; Strathearn, Lane; Kim, Sohye (Frontiers in Psychology, 2019)
The onset of motherhood is characterized by significant psychological and neurobiological changes. These changes equip the mother to care for her new child. Although rewarding, motherhood is also an inherently stressful period, more so for mothers with unresolved trauma. Past research has looked at how unresolved trauma can hamper a mother’s caregiving response towards her infant, which further affects the development of secure attachment in her own infant. The Dynamic Maturational Model of Attachment and Adaptation (DMM) has introduced a unique concept of “attachment reorganization” which can be described as a process whereby individuals with unresolved trauma are transitioning towards attachment security based on their enhanced understanding of past and present experiences. Preliminary results from one of our previous studies have shown that, among mothers with unresolved trauma, mothers who themselves demonstrated “reorganizing attachment” towards security, had infants with secure attachment, thereby indicating the potential to halt the intergenerational transmission of insecure attachment. While this concept is of great clinical relevance, further research is required to assess the benefits of attachment reorganization as a protective factor and its positive implications for child development. Thus, the aim of the current review is to expand on the concept of attachment reorganization in mothers with unresolved trauma from both attachment and neuroscience perspectives. To that effect, we will first review the literature on the transition to motherhood from attachment and neuroscience perspectives. Second, we will use attachment and neuroscience approaches to address deviations from normative experiences during motherhood with a specific focus on the role of a mother’s unresolved trauma. Lastly, we will expand on the concept of reorganization and the promise this concept holds in resolving or halting the intergenerational transmission of trauma from mothers to their children.